Édito - Agnès Grimault-Leprince; Sophie Joffredo-Le Brun; Pascal Plantard (Recherches en Éducation)
Technological change is shaking up the school system, forcing to rethink the way teaching takes place and the relationship with knowledge. This issue proposes to contribute to this undertaking by looking at transformations in teaching-learning practices from the angle of socio-cultural practices and of the appropriation of technologies. Questions of cooperation and autonomy are also at the heart of the analyses. The aim is to articulate the experience of teachers with that of students and their parents. The authors draw in particular on the work of the e-FRAN IDÉE research program (Digital interactions for education and teaching), which considers the transformation of educational digital uses, particularly in schools, with a view to reducing inequalities.